Code of Ethics of Judges as a Guide for the Performance of Good Legal Professions - Zahrany, Amelia; Adji, Salwadita Putri; Rosandi, Albin Aprikiano (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
Indonesia as a state of law must uphold justice properly, therefore how can a judge's profession become an enforcer of justice in Indonesia with the decisions made by a judge while there are many judges in Indonesia who stumble over cases and in deciding a case do not have justice. This research aims to discuss the importance of the position, norms, and role of judges in the judicial system in Indonesia. This research is intended to be one of the reference materials in understanding to the profession of judges. The method of writing in this research is carried out using normative juridical methods by prioritizing a qualitative approach from applicable laws and regulations and secondary data and other library materials. The conclusion of this research explains the position of the judge profession and shows the very important role of the judge profession in the judicial system in Indonesia.